2018
DOI: 10.1016/j.psychres.2018.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability of short-interval intracortical inhibition and intracortical facilitation in patients with schizophrenia

Abstract: Impaired short-interval intracortical inhibition (SICI) elicited by paired-pulse TMS (ppTMS) has emerged as one of the most consistent TMS findings in patients with schizophrenia. Reduction of SICI has been reproducibly found, suggesting that SICI may be a new biomarker indexing the inhibitory dysfunction in schizophrenia. This study evaluated whether SICI has the test-retest reliability suitable for clinical trial and research applications. SICIs, intracortical facilitation (ICF), and other ppTMS effects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 68 publications
3
8
0
Order By: Relevance
“…Trials were randomized and delivered in one session, with intertrial intervals jittered between 4 and 10 s. Participants were evaluated in two sessions about 4 weeks apart. High reproducibility of the paired-pulse effects between the two sessions was was observed and previously reported ( Du and Hong, 2018 ). Therefore, we merged the data from the two sessions to obtain robust and reliable representation of SICI (i.e., 24 trials for test stimulation and 24 trials for SICI).…”
Section: Methodssupporting
confidence: 82%
“…Trials were randomized and delivered in one session, with intertrial intervals jittered between 4 and 10 s. Participants were evaluated in two sessions about 4 weeks apart. High reproducibility of the paired-pulse effects between the two sessions was was observed and previously reported ( Du and Hong, 2018 ). Therefore, we merged the data from the two sessions to obtain robust and reliable representation of SICI (i.e., 24 trials for test stimulation and 24 trials for SICI).…”
Section: Methodssupporting
confidence: 82%
“…Interpretation of the few other studies that demonstrated increased and decreased RMT may reflect disease heterogeneity or the persisting effects of medication. 97 Amplitude of motor evoked potentials Amplitudes of MEPs did not differ between patients with chronic schizophrenia (medicated and unmedicated) and healthy controls, regardless of whether the hand area of the primary motor cortex was stimulated with a suprathreshold intensity, 87 at 120% RMT 79,82 or with the lowest stimulus intensity required to produce maximum MEPs. 94 Similarly, MEPs did not differ between patients (most of whom were medicated) and healthy controls when the motor cortex was stimulated with an intensity intended to elicit an average MEP of 1 mV amplitude (SI-1mV), in either intensity 76,89,97,99 or amplitude.…”
Section: Resting Motor Threshold and Active Motor Thresholdmentioning
confidence: 86%
“…In 15 of the 19, no significant differences in RMT were reported between patients and healthy controls. 54,60,[78][79][80][81][82][83][84][85][86][87][88][89][90] This lack of difference in RMT was observed in patients with chronic schizophrenia but also extended to medication-naive or minimally treated (< 1 month) patients with first-episode psychosis. 91 Lower RMT values (indicating increased corticospinal excitability) were reported in only 1 study of medicated patients with schizophrenia, but also in patients with major depressive disorder and manic disorder.…”
Section: Resting Motor Threshold and Active Motor Thresholdmentioning
confidence: 99%
See 2 more Smart Citations